Metode Pembelajaran Kontektual sebagai Upaya Peningkatan Motivasi Belajar Akuntansi Mahasiswa Universitas Dharmawangsa - Siregar, Lukman Hakim; Junaidi, Listya Devi; Atika, Diyah (Universitas Nahdlatul Ulama Surabaya, 2020)
Based on midterm exam results there are still many students who get grades below the graduation average. As for several factors that cause, among others: students are very difficult to understand the concept of accounting, lack of motivation for students to study accounting and students are more passive and less able to work together in groups. This study uses class action methods and quantitative research methods, namely using multiple linear regression analysis. The location of the study was conducted at the University of Dharmawangsa Medan. The data source of this research is using primary data and secondary data. The stages of this research process are class action, data quality test, classic assumption test and hypothesis test. The results of this study that in the application of contextual learning have not been fully carried out by Accounting lecturers because they have not fully understood how the contextual learning method is. Simultaneously, contextual learning methods have a significant effect on motivation, but contextual learning methods do not affect student learning outcomes.